Aspects of social life in the Middle Maghreb in the late Middle Ages Through the books of documents "contracts" - hannache, fahima (The Algerian Historical Journal, 2026)
Documentation books, despite their jurisprudential nature, are considered one of the most important sources that researchers have come to rely on in writing Maghrib history in the Middle Ages. This is because it carries within it a documentary stock that can be used to study several aspects of Maghribin civilizational history (social, cultural, economic). This study aims to reveal the importance of document books in enriching the resources of historical research, especially in its marginalized aspects related to people’s daily lives and society, which have been neglected by traditional autography, by employing the analytical and inductive historical method to interrogate the cognitive content in order to identify aspects of social life. The Middle Maghreb in the late Middle Ages.